2022
DOI: 10.21307/ane-2021-021
|View full text |Cite
|
Sign up to set email alerts
|

Brain‑derived neurotrophic factor and nitric oxide contribute to protective effects of rosiglitazone on learning and memory in hypothyroid rats

Abstract: The effects of the well-known peroxisome proliferator-activated receptor gamma (PPAR-γ) agonist rosiglitazone (Rosi) on brain-derived neurotrophic factor (BDNF), nitric oxide (NO), and learning and memory were investigated in hypothyroid rats.Hypothyroidism was induced in immature Wistar rats by administration of propylthiouracil in drinking water. Rats were divided into four groups: control, hypothyroid, and hypothyroid treated with Rosi at doses of 2 mg/kg or 4 mg/kg. Memory was then assessed by the Morris w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…Based on the results of the present study, we also found that treating animals with POG or RSG lead to a decrease in NO levels in the hippocampal tissue, which can be considered as one of the possible mechanisms for useful effects of activating PPARγ. These results are in agreement with our previous studies, which showed that POG or RSG decreased NO levels in brain tissues (Baghcheghi et al 2021, Franco et al 2006, Venditti & Di Meo 2006. Therefore, in the present study, we can imply that POG or RSG, probably by diminishing NO, prevent apoptosis and LTP impairment in hippocampal tissue of hypothyroid rat.…”
Section: Discussionsupporting
confidence: 94%
“…Based on the results of the present study, we also found that treating animals with POG or RSG lead to a decrease in NO levels in the hippocampal tissue, which can be considered as one of the possible mechanisms for useful effects of activating PPARγ. These results are in agreement with our previous studies, which showed that POG or RSG decreased NO levels in brain tissues (Baghcheghi et al 2021, Franco et al 2006, Venditti & Di Meo 2006. Therefore, in the present study, we can imply that POG or RSG, probably by diminishing NO, prevent apoptosis and LTP impairment in hippocampal tissue of hypothyroid rat.…”
Section: Discussionsupporting
confidence: 94%
“…In PND 9, the statistical analysis by one -way ANOVA at p≤0.05 showed that the mean time that pups were needed to reach the home bedding was (10.33 ± 3.02) sec in pups of control group, while those pups of hypothyroid groups(hypothyroid without treatment , hypothyroid treated with levothyroxine and hypothyroid treated with Ashwagandha Roots extract) were (40.83±14.428), (38.13±14.397), and (41.6±11.415) sec., respectively. These results showed that the time required for the pups of hypothyroid groups (2,3,4) to reach maternal bedding was much longer than time of the control group pups (1). Fig.…”
Section: Behavioral Tests Nest-seeking Resultsmentioning
confidence: 88%
“…Severe cognitive impairment comes from congenital hypothyroidism [2]. Moreover, there is evidence that neurocognitive impairments may continue even when early detection and therapy have been found to improve many of these problems [3]. Numerous studies show that thyroid hormones influence a variety of behaviors throughout life by acting in multiple brain areas both during development and in maturity [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, different studies have also affirmed an oxidative stress status followed by hypothyroidism. [ 12 13 ] It has been well documented that experimentally induced hypothyroidism leads to an imbalance of production ROS by mitochondria and oxidant enzymes and, scavenging of ROS by the antioxidant system in tissues like the liver interrupted. [ 14 ] Furthermore, it was shown that acute liver failure is connected with enhanced blood endotoxins and pro-inflammatory cytokines and chemokines that are followed by dysfunction of the thyroid gland.…”
Section: Introductionmentioning
confidence: 99%